پەیبردن بە جیاوازیى نیوان چەند هونەرێکى ڕەوانبێژى - سالار, عبدالسلام (Sulaimani Journal for Humanities, 2003)
Since the last contribution of ancient experts, such us Skaki, rhetoric has been stepped many phases apace towards perfection, There after rhetoric witnessed no any mentionable development, even more, The later eloquents' efforts were consisted in relating what had been mentioned before and somtimes resorted to the reuse of the old exampels when demonstrating arts of rhetoric. After comparing the old contributions to rhetoric to what have been added to it, We observed in this research, Ther were a mix between some of the arts of rhetoric by the modernist, In order to avoid such a mix between the arts of rhetoric and to duff rentiate them from each other, We prefered to dedicate this research, Which entitled (), to discriminate among some arts of rhetoric such as between: - Verbal and Mental figurative. - The three types of Meiaphare (declarative,............,?). - Metaphere and Metonymy. - Wrapping, publishing and asimilation. After analysing what we could have reached of conclusion in this research, we depended an index of resources on which we depended on for writing the research with a brief about the research in both Arabic and English language.